IMPROVING THE COMPETENCE OF THE DISABILITY INCLUSION GROUP THROUGH PHYSICAL THERAPY TRAINING IN NGAWONGGO VILLAGE, MALANG REGENCY - Mukhammad Soleh; Marsudi Dedi Putra; Imam Ropi; Himawan Estu Bagijo; Regitha Putri Erlanha; Siti Naharotun Nikmah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Inclusive villages provide space for minorities, namely people with disabilities, to have equal rights and obligations, equal dignity and status, and have the same role and position in the lives of people in the village. The Ngawonggo Village Government, Malang Regency, has sought legal protection for people with disabilities by establishing Village Regulation Number 2i of 2023 concerning the Establishment of Village Disability Inclusion Groups. The method used is physical therapy training for groups of people with disabilities. The result of this community service is in order to optimize the realization of the tasks and functions of inclusion groups as an effort to accelerate independence for people with disabilities through physical therapy training.